Rebuilding to shape a better future: the role of young professionals in the public health workforce - Brian Li Han Wong; Ines Siepmann; Tara T. Chen; Shelby Fisher; Tobias S. Weitzel; Naomi L. Nathan; Diah S. Saminarsih (BMC, 2021)
Abstract The COVID-19 pandemic has made clear the extreme needs of the public health workforce. As societies discuss how to build up the capacity and infrastructure of their systems, it is crucial that young professionals are involved. Previous attempts to incorporate young professionals into the public health workforce have wrestled with inaccessibility, tokenisation, and a lack of mentorship, leading to a loss of potential workforce members and a non-representative workforce that reinforces systemic societal exclusion of diverse young people. These barriers must be addressed through robust mentorship structures, intentional recruitment and continuous support, as well as genuine recognition of the contributions of young professionals to build the sustainable, interdisciplinary, unified public health that is necessary for the future.